P081 Transcranial electric stimulation guided by dipole forward simulation. Issue 3 (March 2017) - Hunold, A.; Schellhorn, K.; Haueisen, J.
Abstract : Introduction: Transcranial electric stimulation (TES) is a non-invasive technique driving small currents from laminar electrodes to the brain eliciting modulation of neuronal activity. Applications of TES in therapy of neurological and psychiatric disorders or neuroscience require implementations of focused TES to target single specific brain areas or a specific node in a functional brain network. Objectives: Aiming at such specific TES stimulations, we introduce a new technique based on the idea of reciprocity, where targeted TES is guided by resampling electric field features originating from an electric current dipole in the target area. Materials & methods: We derived a five compartment finite element method head model from a magnetic resonance imaging dataset. Electrode patches of 4 cm by 4 cm at 19 positions according standard EEG positions completed the computation model. We computed the current density in the brain and the electric scalar potential on the scalp surface of a volunteer produced by a dipole in the target area. The resulting minima of the current density distribution were used to guide a TES setup. The maximum and minimum of the potential on the scalp surface served for polarity selection of the TES electrodes. We compare our results to those obtained with a distributed beam former TES simulation for the same target area. Results: The TES setup targeting the position of a dipole located in the left hand knob and oriented in anterior-posterior direction involved the electrodes at positions C3 and Pz as anode and cathode. Our new method produced a current density distribution in the brain with the maximum at the target area. The orientation of the current density vector in the target location deviated 39 degree from the orientation of the initially simulated dipole. The current density magnitude in the target location was 0.03 A/m for the bipolar TES setup with an applied current strength of 1 mA. The beam former TES produced the maximum of the current density in a brain area inferior to the target area. For the beam former TES, the orientation of the current density vector in the target location coincided with the orientation of the initially simulated dipole and the magnitude in the target location was 0.01 A/m. Conclusion: Our new approach for targeted TES is simple to implement and might be used with other forward solvers. Due to its simplicity, it can guide future clinical and basic research TES studies.